El juego en el desarrollo del área cognitiva de los niños y niñas de 4 años de la Unidad Educativa Gregoriano en la ciudad de Guayaquil - Ponce Bustamante, María Fernanda (2016)
This project pursues the purpose that, throughout the game, to develop the cognitive area for children from 4 years of the educational unit "Gregorian". So, it is part of a scientific diagnosis that combines methods and techniques to learn to what extent applies the game to contribute in the development of the students. The study, seeks to have the educators take to strengthen the capacities of their kindergarten in the cognitive area, through the implementation of activities with objectives previously planned, in tune with the curricular requirements of children's education in Ecuador….